Rural Broadband and the Unrecovered Cost of Streaming Video Entertainment - Roslyn Layton; Petrus Potgieter (International Telecommunications Society (ITS), 2021)
The paper described the challenge of provision of rural broadband provision by examining the economics of 4 fiber to the home networks in different parts of the US. It shows how streaming video entertainment is the largest and growing category of traffic and which puts unique demands on the network. The paper described the history, policy, and economics of traditional end user pricing models flat, and uniform (over service area) based on speed tiers, and their shortcomings to support continued investment. It introduced the notion of the Big Streamers, the five largest video streaming providers and their content distribution practices. The document also reviewed the components of a rural broadband network. It reviewed traffic data from the networks, calculated revenue and cost, defined amounts of overage, and projected future shortfalls. This analysis demonstrates that rural networks are heavily burdened by huge volumes of streaming content which is turned into revenue not by the broadband providers but by the Big Streamers. The policy solutions section introduced the three types of response and their implications. The current model of flat and uniform (over service area) pricing (even with subsidy) is likely to become unsustainable for rural broadband provision. The paper contributes to the ongoing policy discussion of rural broadband and closing the digital divide.
Keywords: 330